Evaluating the Impact of Online Learning Systems on Institutional Performance in Kenya’s Public Universities - Gachau, Agnes (International Journal of Professional Practice, 2026)
The study examined how online learning affects the performance of public universities in Kenya, focusing on how Learning Management Systems (LMS), institutional readiness, and implementation efficiency influence academic and institutional outcomes. Although online learning has been globally recognized for expanding access and flexibility, evidence from developing countries, including Kenya, shows inconsistent adoption and limited effectiveness due to infrastructural and pedagogical challenges. The study addressed this gap by analyzing the relationship between online learning systems and university performance. Specifically, it sought to: (i) examine the effect of online learning systems on academic performance, and (ii) assess institutional readiness and efficiency in implementing online learning. The study covered seven purposively selected public universities, involving 537 respondents (384 students and 153 staff). Using a descriptive quantitative research design, guided by pragmatism and deductive reasoning, data were collected through structured questionnaires and interviews, supported by secondary documents. Stratified and simple random sampling ensured representativeness. Reliability testing using Cronbach’s alpha yielded values between 0.762 and 0.778, confirming strong internal consistency, while expert review and factor analysis validated the instruments. Data were analyzed using SPSS, employing descriptive and inferential techniques, including correlation, ANOVA, and logistic regression. The research was anchored in the Technology Acceptance Model (TAM) and the Diffusion of Innovations (DOI) theories, which explain user adoption behavior and the institutional diffusion of educational technologies. Findings revealed that LMS improved openness, communication, and institutional visibility, though efficiency and resource sharing remained inconsistent. The study concludes that online learning has positively influenced university performance but recommends greater investment in ICT infrastructure, staff training, and innovation-driven learning environments.